Yield Function of the DOSimetry TELescope Count and Dose Rates Aboard the International Space Station - A. S. Caprotti; M. Brüdern; S. Burmeister; B. Heber; K. Herbst (Space Weather)
Abstract The Earth is constantly hit by energetic particles originating from galactic sources. The flux of these particles is altered by the magnetized solar wind in the heliosphere and the Earth's magnetic field. For this reason, the ability of a particle to approach a spacecraft in low Earth orbit depends on its energy and the position of the spacecraft within the Earth's magnetosphere. Moreover, there are some areas (radiation belts) where the particles are trapped for a long time and, therefore, the flux of energetic particles is particularly high. Occasionally, solar energetic particles contribute to the energetic particle flux too. DOSimetry TELescope (DOSTEL) is one of the instruments aboard the International Space Station (ISS) that monitors the radiation field within the European module Columbus. Because being installed inside the ISS, particles produced by the interaction between the “primary” radiation and the ISS materials are also measured. To describe the observations in such a complex radiation field, we follow the method by Caballero‐Lopez and Moraal (2012, Journal of Geophysical Research, 117[A12], A12103. doi:10.1029/2012JA017794) to compute the so‐called yield function using precise measurements of the proton and helium energy spectra obtained by alpha magnet spectrometer and the systematic variation of the DOSTEL measurements within the Earth's magnetosphere.